Relief of intractable pruritus with romidepsin in patients with cutaneous T‐cell lymphoma: A series of four cases. Issue 2 (4th January 2019) - Poligone, Brian; Rubio‐Gonzalez, Belen; Querfeld, Christiane
Abstract: Cutaneous T‐cell lymphomas (CTCL) are a relatively rare and heterogeneous group of non‐Hodgkin lymphomas that typically present in the skin. The majority of patients with CTCL experience pruritus, which can interfere with daily activities, significantly impact quality of life, and is typically uncontrolled by standard anti‐itch therapies. Several lymphoma treatments have reported anti‐pruritic effects including romidepsin, a potent class 1 selective histone deacetylase inhibitor approved for the treatment of patients with CTCL who have had at least one prior systemic therapy. Here, we describe the cases of four patients with debilitating and refractory pruritus that were resolved with romidepsin. Resolution of pruritus was observed in both clinical responders and nonresponders, and dose modification was used successfully to manage adverse events and for maintenance treatment. The potential for pruritus relief with romidepsin should be considered when treating patients with CTCL.